World English 2 / Kristin L. Johannsen & Rebecca Tarver Chase ; Rob Jenkins, series editor - Johannsen, Kristin L.
The new edition of four-level World English series brings the most amazing stories about our planet and compelling ideas from around the world to the integrated-skills classroom.